An ultra-sensitive localised surface plasmon resonance fibre device for environmental sensing based upon a structured bi-metal coating - Allsop, Thomas P.; Neal, Ron M.; Mou, Chengbo; Kalli, Kyriacos; Webb, David J. (My University, 2014)
We demonstrate a bi-metal coating (platinum and gold or silver) localised surface plasmon resonance fibre device that produces an index spectral sensitivity of over 11,000 nm/RIU, yielding an index resolution of 5×10-6in the aqueous index regime, consisting of a structured multi-layered thin film on D-shaped fibre.
Keywords: Metal coatings; Optical fibers; Sensors; Spectroscopy